ANALISIS FAKTOR PENYEBAB JEBOLNYA TANGGUL SITU GINTUNG - Harsoyo, Budi (Jurnal Air Indonesia, 2010)
Spatial and hidrology analysis has been done to find out the main factor of causing the burst of Situ Gintung dam incident on March 27, 2009. Spatial analysis was done to get some parameters that needs as input for hidrology analysis. The analysis results indicating that rain fall actually was be one of cause factors that incident, but not as the main factor. The condition of dike which already broken as the consequence of its life time and also the condition of spill way which has not function as like as innitialy built by Nederland Goverment, is more as principal factor of causing the burst of Situ Gintung dam incident. Keywords : Situ Gintung, analysis, spatial, hidrology, cause factors.